Reading Literacy: Difficulty In Understanding Problems In Mathematical Problem Solving - Ety Mukhlesiyeni (PGMI IAIN Lhokseumawe, 2024)
Students' capacity to solve problems is impacted by their low reading proficiency. This study aimed to characterize how students' reading literacy affected their comprehension of problems, which is the initial step in problem solving. 39 elementary school pupils in the fifth grade served as the research subjects for the descriptive analysis research method. The data analysis results demonstrated that students with high category abilities could comprehend the meaning of problems when they were solving them, but they needed to be meticulous and deeply involved in the difficulties they were working on. Due to their limited capacity for issue interpretation, students in the medium and low category abilities were not yet able to answer problems as a whole.